Let Bygones be Bygones? Political Regimes and Personalities in Germany - Markus Pannenberg; Tim Friehe; Michael Wedow (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper investigates the influence of political regimes on personality, using the separation of Germany into the socialist GDR and the democratic FRG and its reunification in 1990 as a natural experiment. We establish significant differences between former GDR and FRG residents regarding important attributes of personality (particularly neuroticism, conscientiousness, openness, and the locus of control). To understand the influence of the GDR's political regime on personality, we test an important channel by exploiting regional variation in the number of unofficial state-security collaborators across East German counties. Our results indicate that local surveillance intensity is an important determinant of the personality of former GDR citizens indeed. The observed significant differences in personality imply that former citizens of the GDR have economic prospects very different from former FRG citizens and help to understand behavioral differences established in the prior literature.
Keywords: D03; D12; D63; 330